PEMAKAIAN ISTILAH DALAM PERTANDINGAN SEPAK BOLA YANG DISIARKAN MELALUI RADIO - Tuti Cahyanti; Basuki Basuki (CARAKA, 2018)
The aim of this study is presented as follows: 1) To describe the terms that used by the announcer in football match that broadcasted through radio. 2) to describe the function of the terms by the announcer in football match that broadcast through radio. 3) to identification background of the terms that used by the announcer in football match that broadcasted through radio. This research included in qualitative descriptive. The dataÂ  form in this research is a sentence which is consist of the terms that used by the announcer . The data resource in this research is the announcerâ€™s language that used in football match through radio. The instrument of this research is science concept which is relataed with the problems in this research. Data collection technique that used in this research is simak method with the basic technique is tapped technique, Simak bebas libat cakap technique, record technique and noted technique. Data analysis technique that used in this research is padan method and continued with pilah technique. Next is the method of presentation data analysis result using informal presentation method. The result of this research is presented as follows: 1) The variety terms that used the football announcer through radio was classified into two: firstly, typical terms in football that derivied form different environment. Secondly, football terms derived from foreign language. 2) the term function that used football announcer in radio is general function and special function. Some Factors that made the terms of football announcer was influenced by time, place, football match situation, the participants that involved in substitutions. Refers to the speech and speech content from the football announcer in radio. Refers to the tone, manners and the spirit to deliver the message, refers to oral language track, refers to the norm or the rules in interaction and the way the announcer deliver the message orally in radio.Â